A Longitudinal Study of Road Traffic Noise and Body Mass Index Trajectories from Birth to 8 Years. Issue 5 (September 2018) - Weyde, Kjell Vegard; Krog, Norun Hjertager; Oftedal, Bente; Magnus, Per; White, Richard; Stansfeld, Stephen; Øverland, Simon; Aasvang, Gunn Marit
Abstract : Background: Being overweight constitutes a health risk, and the proportion of overweight and obese children is increasing. It has been argued that road traffic noise could be linked to adiposity through its influence on sleep and stress. Few studies, to our knowledge, have investigated whether noise and adiposity are associated. Most of them were on adults, and we are not aware of any longitudinal study using repeated measures. Objectives: The present longitudinal study investigated whether road traffic noise exposures in pregnancy (N = 6, 963; obs = 22, 975) or childhood (N = 6, 403; obs = 14, 585) were associated with body mass index (BMI) trajectories in children. Methods: We obtained information on BMI and covariates from questionnaires used in the Norwegian Mother and Child Cohort Study, Statistics Norway, and Medical Birth Registry of Norway. We modeled road traffic noise for the most exposed façade of children's present and historical addresses at 6 time points from pregnancy to age 8. We investigated effects on BMI trajectories using repeated measures and linear mixed models. Results: The results indicated that BMI curves depended on road traffic noise exposure during pregnancy, but not on exposure during childhood. Children in the highest decile of traffic noise exposure had increased BMI, with 0.35 kg/m 2 more than children in the lowest decile, from birth to age 8 years. Conclusions: The results indicate that exposure to road traffic noise during pregnancy may be associated with children's BMI trajectories. Future studies should investigate this further, using anthropometric measures such as waist-hip ratio and skinfold thickness, in addition to BMI.